IMPLEMENTASI SMIDEP (THE PROJECT ON SMALL AND MEDIUM INDUSTRI DEVELOPMENT BASED ON IMPROVED SERVICE DELIVERY) DALAM PENGEMBANGAN INDUSTRI TENUN ULOS DI SAMOSIR - Aditia Fernando Tambunan; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research focuses on examining technical cooperation between Indonesia and Japan in the development of the Ulos Weaving Industry in Samosir in a program called The Project on Small and Medium Industry Development Based on Improved Service Delivery (SMIDeP) based on the medium-term national development plan (2010-2014 ) and Indonesia's long-term development plan (2005-2025). Based on a survey of the project's expert team, Samosir Regency is one of the target areas with the potential for developing Service Delivery-based industries.This research was developed based on the Liberalism framework which is supported by the theory of international cooperation with the level of state analysis, where the state becomes the main actor in international relations. This study uses qualitative methods with data collection techniques through library research (Library Research).The implementation of the SMIDeP project in Samosir through capacity building, promotion and marketing activities and strengthening the Joint Business Group (KUB). The project made an important contribution to the development of the Weaving Ulos industry in Samosir Regency, such as product diversification and increased product sales. Keywords: Implementation, SMIDeP, Service Delivery, Tenun Ulos Industry, Samosir.